G402(P) The completion of advance care plans. (12th March 2018) - Renton, K; Mayer, A; McElligott, F
Abstract : Aims: To establish the availability and completion of Advance Care Plans (ACP) in paediatric palliative hospice patients. To review changes to this in light of new guidance and following recommendations from a previous audit. ACPs are a valuable resource for patients, their families and healthcare professionals. Between the first and second audits there were two significant implementations. The National Institute for Health and Care Excellence (NICE) published guidelines about end of life care in children and young people in 2016. One of their quality statements is that all children with a life-limiting condition should be involved in developing an ACP. The second implementation was the adoption of the Children and Young Person's Advance Care Plan (CYPACP) by the local palliative network. Methods: All patients under the care of the palliative medical team were identified. Patients referred within the previous two months were excluded. Notes of all patients were reviewed and computer records accessed. The presence of an ACP was noted and, if available, was reviewed against set standards based on national recommendations. This included items such as patient identifiers, documented discussions about place of care, signature completion, and others. The first audit was done in December 2016 (n=41), with a repeat audit (to complete the cycle) in September 2017 (n=41) following institution of recommendations from the first audit. These recommendations included implementation of a teaching programme about using the new proforma (CYPACP). Results: In 2016, 80% of patients had ACPs. This improved in 2017 to 88%. In 2017, 25% were on CYPACP proforma compared to 6% in 2016. Patient identifiers were consistently well completed in both audits. Many ACPs were not signed (62% in 2016, 78% in 2017) which poses risk and challenges for nurses expected to follow documented recommendations. Discussion regarding place of care/death was completed in 100% of cases in 2017, compared to 79% in 2016. Conclusion: The process of writing ACPs is time intensive and transfer to new documentation is a significant undertaking. However, the introduction of the CYPACP has led to more comprehensively completed ACPs, particularly around place of care/death.